Influence Zalak Fruit Skin Extract (Salacca zalacca) On Lipid Profiles in Type 2 Diabetes Mice - Suntara, Ditte Ayu; Hutapea, Albert M; Napiah, Ali; Halim, Susanna (Future Science, 2024)
Salak peel was found to contain various phytochemical substances, including saponins, alkaloids, flavonoids, steroids, and phenolics. There is a common belief that certain active chemicals have antioxidant properties and have the potential to reduce glucose levels in the human body (Sandhar et al., 2011). Objective study For investigate the impact skin snake fruit on lipid profile, on T2DM mice. Study laboratory experimental, with quasi-experimental, in a manner special use Pretest-Posttest design. Group Experiment: 15 mice Wistar male, which is divided become three group. Group 1 works as negative control (TP), group 2 involved metformin (M) administration, focus group 3 on delivery extract skin Salak (EKS). Treatment given for 3 weeks, obtained results happen change average lipid profile in each point measuring Where change No significant increase or decrease on TP, M, EKS groups, with p?0.05. Regeneration of pancreatic beta cells No influenced by presence metabolites secondary, including flavonoids, phenolics, and saponin, in extract ethanol skin snake fruit. And no can hinder conversion superoxide become hydrogen superoxide through the transformation chain. Besides that, flavonoids facilitate Power pull radical free to the hydrogen atom from group hydroxyl aromatic, so No help in a way significant in elimination they from body through system deletion.